A Review of Toxoplasmosis in Humans and Animals in Libya - Elsalem, Rugaia (Journal of Pure & Applied Sciences, 2024)
Toxoplasmosis is a widely distributed zoonotic infection, caused by an obligate intracellular protozoan parasite Toxoplasma gondiiin both humans and animals. The review summarizes published data on mode of infections, prevalence, life cycle, clinical aspects diagnosis, and risk factors of T. gondii in Libya. There is no adequate information exists on the mode of T. gondii transmission in Libya. Presence of stray cats and rodents in the houses and farms in different Libyan cities, probably play an important role in the maintaining the life cycle of T. gondii in the region. Libyan people might be also getting infection of T. gondii either by ingesting raw and undercooked grilled meat of lamb on festive occasions and sacrifice feasts and very often in restaurants on road side or by handling contaminated meat. Handling of infected meat by abraded hands at home might be transmitting toxoplasmosis to some extent through blood from broken skin especially among women in Libya. Diagnosis of T. gondii infection in Libya is based on serological detection of specific anti- Toxoplasma immunoglobulin, using different serological tests which have varied sensitivity and specificity in place to place. Various serological tests showed that toxoplasmosis is prevalent in eastern and western regions compared to southern parts of different Libyan localities from past few decades without any health education and control programmed. Prevalence of anti-ToxoplasmaIgG was more than anti-Toxoplasma IgM among pregnant women and patients. Variations in seroprevalence of T. gondii in Libya seem to correlate to lifestyle of cats (stray vs. pet), serological test utilized, climatic conditions, category of patients the with eating and hygiene habits of a population and other undefined factors. Little is known on the seroprevalence of toxoplasmosis in livestock. The sheep showed high seroprevalence and are suitable host for T. gondii in Libya.